Periorbital Purpura: A Key Finding in Identifying Hematological Disorders - Ryohei Ono; Togo Iwahana; Kaoruko Aoki; Hirotoshi Kato; Yoshio Kobayashi (Clinical Case Reports, 2025)
ABSTRACT Periorbital purpura, also known as “raccoon eyes,” is the key finding in identifying hematological disorders such as amyloid light chain amyloidosis, multiple myeloma, or monoclonal gammopathy of undetermined significance.